Mini-laparoscopic pyeloplasty in adults: Functional and cosmetic results - Pelit, Eyyup Sabri; Ciftci, Halil; Kati, Bulent; Yagmur, Ismail; Ordek, Eser; Arslan, Erkan; Yeni, Ercan (Urology Journal, 2018)
Purpose: The study objective was to evaluate the safety and efficacy of mini-laparoscopic pyeloplasty (mLP) in an adult population and to demonstrate the functional and cosmetic results. Methods: Data for 29 patients (19 men and 10 women) undergoing mLP for ureteropelvic junction obstruction (UPJO) from May 2014 to December 2016 in Turkey were collected in this prospective study. Inclusion criteria were age ? 18 years, body mass index (BMI) ? 30 kg/m2 and primary UPJO, and no previous surgery on the affected kidney or previous abdominal surgery. Postoperative Visual Analogue Scale scores and the Patient Scar Assessment Questionnaire (PSAQ) were used. Demographic data, perioperative parameters, complications, and postoperative functional and cosmetic results were recorded. All statistical analyses were done by SPSS software. P value of <05 was considered statistically significant. Results: Twenty-nine adults with a mean age of 29.4 ± 10.2 years (19–38 years) were included. The patients’ mean BMI was 22.4 ± 4.3 kg/m2 (a range of 16–29 kg/m2). The procedures were performed using three ports (one 5 mm port for the camera and two 3 mm ports). Mean operative time was 119 ± 28.5 minutes (85–144 minutes). Major complications were not observed, as per the Clavien-Dindo classification of surgical complications (grades IV–V). The mean VAS score was 1.2 ± 0.2 points. Functional obstruction was reported in one patient on renal scintigraphy at 12 months postoperatively. The success rate of mLP was 97%. The minimum and maximum PSAQ scores at month 3 postoperatively were 24 and 86, respectively. All the patients were satisfied with the intervention and with their cosmetic results. Conclusion: mLP is a safe, effective and feasible treatment method for UPJO in adult patients. This treatment modality offers excellent cosmetic and functional results following treatment for UPJO.